Formulation and In Vitro Characterization of Solid-self Nanoemulsifying Drug Delivery System of Atorvastatin Calcium - Reddy, Dr. M. Sunitha (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of present study is formulation and in vitro characterization of solid-self nanoemulsifying drug delivery system (S-SNEDDS) of atorvastatin calcium. Atorvastatin calcium is a BCS Class II HMG Co-A reductase inhibitor also called as statins used in the treatment of high cholesterol. The solubility and dissolution profile of atorvastatin calcium which has poor aqueous solubility and low bioavailability was improved using SNEDDS. Materials and Methods: The solubility of drug in various oils, surfactants and cosurfactants were analyzed and peceol as oily phase, labrasol as surfactant, polyethylene glycol 400 as cosurfactant were selected for the formulation. To obtain ideal self-emulsification region, pseudo-ternary phase plots were constructed. Liquid SNEDDS were prepared, evaluated and two formulations PL1PEG4 A1, PL1PEG4 A2 were found to be stable and optimum. Results and Discussions: The formulation consisting of peceol, labrasol, PEG400 and drug 20 mg was selected for converting into S-SNEDDS using crospovidone as a carrier. Particle size distribution, zeta potential, and polydispersity index were characterized and found to be 36.22 nm, −1.32 mV, and 0.164, respectively. Dissolution tests were performed, and percentage drug release was found to be 91.7%. Accelerated stability studies were performed RH 75% ± 5% and 40°C ± 2°C for 1 month and were found to be stable.